When I Masturbate - Íris Stefanía Skúladóttir 1986- (2019)
“When I Masturbate” by Íris Stefanía Skúladóttir is her graduation work from the Department of Performing Arts at Iceland University of the Arts. Iris has chosen to use story circles as a way for women to open up and discuss masturbation and other sensitive topics. There are two kinds of story circles that she is working with. The first is a closed story circle for women only, where women get to listen to the stories of other women, as well as share their own experiences. The second is an open story circle for the public to listen to the women’s stories collected in the closed circles. The relation between the open and closed circles is very purposeful. The closed circle is a safe space that creates an all female gaze, where women can listen to the voices of other women, speaking freely about their relationship to pleasure and desire as women living in the patriarchy. The open circles are about giving everyone an opportunity to listen and learn from these stories – and this situation calls for a different kind of care and precision. In the open story circles representation of women and their real life experiences comes into contact with a more aggressively present male gaze – and how that is negotiated has to be engineered with different concerns and priorities in mind. Iris is more selective about which stories are told, and which are not, she thinks carefully about the mode of delivery, who it is told by and for whose ears. It is very important that stories still maintain their own integrity as stories told by women for other women – but at the same time become accessible for other ears and gazes. “When I Masturbate” will travel around the world and the stories collected will end up on a database of stories at www.whenimasturbate.world Long live pleasure! Bio Íris Stefanía Skúladóttir (1986) Íris is an artist and curator interested in sexual ehavior. In her practice she has been focused on women and their pleasures, taboos, shame and desires. The masturbation is a centre point in Iris’s practice.? She has ...